2011
DOI: 10.1038/ncomms1470
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-enabled epitaxy through control of growth mode with chemical boundary conditions

Abstract: Property coupling at interfaces between active materials is a rich source of functionality, if defect densities are low, interfaces are smooth and the microstructure is featureless. Conventional synthesis techniques generally fail to achieve this when materials have highly dissimilar structure, symmetry and bond type-precisely when the potential for property engineering is most pronounced. Here we present a general synthesis methodology, involving systematic control of the chemical boundary conditions in situ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…During growth, this Cl ML must remain, at least partially, on the MgO surface, similar to the behavior of other film growth "surfactants." 25,55 The use of Cl as a surfactant for (111) MgO surfaces is consistent with prior observations. Koranyi et al have FIG.…”
Section: Investigation Of the Mechanism For Saesupporting
confidence: 76%
See 3 more Smart Citations
“…During growth, this Cl ML must remain, at least partially, on the MgO surface, similar to the behavior of other film growth "surfactants." 25,55 The use of Cl as a surfactant for (111) MgO surfaces is consistent with prior observations. Koranyi et al have FIG.…”
Section: Investigation Of the Mechanism For Saesupporting
confidence: 76%
“…We see a similar need to provide a constant H 2 O surfactant flux when growing smooth, -OH terminated (111) MgO epilayers on GaN. 25 If the H 2 O flux is removed at any point during film growth, the surfactant effect is lost and a rapid transition from 2D to 3D growth mode occurs. Indeed, the concentrations of Cl are noticeably lower on the surface of the thick MgO films [ Fig.…”
Section: Investigation Of the Mechanism For Saementioning
confidence: 99%
See 2 more Smart Citations
“…The surfactant hydrogen changes its position and remains on the surface during the growth process, providing a dynamical solution for the polarity constraints throughout the growth of MgO(111), by effectively healing (quenching) the surface dipole moment and thus lowering the surface energy. At the same time, in the presence of a water-based surfactant, Paisley et al [11] have demonstrated the surfactant-assisted growth of atomically flat polar CaO(111) oxide film with arbitrary thickness by MBE growth of CaO(111) on GaN(0001). In addition, they have used ab initio thermodynamic calculations to predict that in the presence of the water surfactant, flat CaO(111) surfaces are stabilized by hydroxylation during surfactant-assisted growth at temperatures below 253 o C. However, the water-based surfactant-assisted growth mechanism remains unknown.…”
mentioning
confidence: 99%